PERBEDAAN PENGGUNAAN E-WALLET OLEH MAHASISWA LAKI-LAKI DAN PEREMPUAN - Pramesthi Bella Hasna; Hellna Alodia Ivana; Aulia Sari Itsna (Jurnal Ilmu Administrasi Bisnis, 2024)
E-Wallet is one of the technological innovations widely adopted by the Indonesian society, including students. E-Wallet provides various benefits to students, including ease of transactions, transaction security, and cost savings. There are differences in the usage of E-Wallet between male and female students. This article aims to explore the frequency, purpose, and reasons for using E-Wallet among male and female students. The research method employed is qualitative, with active students from the Faculty of Economics and Business at Universitas Sebelas Maret as informants. The data collection technique used is a questionnaire. The results of the study, involving 75 respondents with a percentage of 40% male students and 60% female students, indicate differences in the usage of E-Wallet between male and female students in terms of frequency and purpose of use, while there is similarity in the aspect of reasons for usage. The primary factor driving the use of E-Wallet by both groups of students is the ease of transactions.Keywords: E-Wallet; Male Student; Female StudentE-Wallet merupakan salah satu inovasi teknologi yang banyak diadopsi oleh masyarakat Indonesia, termasuk di kalangan mahasiswa. E-Wallet memberikan berbagai manfaat kepada mahasiswa, termasuk kemudahan dalam transaksi, keamanan transaksi, dan penghematan biaya. Terdapat perbedaan dalam penggunaan E-Wallet antara mahasiswa laki-laki dan perempuan. Artikel ini bertujuan untuk mengeksplorasi frekuensi, tujuan, dan alasan penggunaan E-Wallet di kalangan mahasiswa laki-laki dan perempuan. Metode penelitian yang digunakan adalah kualitatif, dengan mahasiswa aktif dari Fakultas Ekonomi dan Bisnis Universitas Sebelas Maret sebagai informan. Teknik pengumpulan data yang digunakan adalah kuesioner. Hasil penelitian, melibatkan 75 responden dengan persentase 40% mahasiswa laki-laki dan 60% mahasiswa perempuan, menunjukkan perbedaan dalam penggunaan E-Wallet antara mahasiswa laki-laki dan perempuan dari segi frekuensi dan tujuan penggunaan, sementara terdapat kesamaan dalam aspek alasan penggunaan. Faktor utama yang mendorong penggunaan E-Wallet oleh kedua kelompok mahasiswa adalah kemudahan dalam transaksi.Kata Kunci: E-Wallet ; Mahasiswa Laki-Laki; Mahasiswa Perempuan